Performance prediction of chalcopyrite-based dual-junction tandem solar cells. (October 2017) - Kim, Kihwan; Yoo, Jin Su; Ahn, Seoung Kyu; Eo, Young-Joo; Cho, Jun-Sik; Gwak, Jihye; Yun, Jae Ho
Graphical abstract: With the SCAPS-1D simulation package, we assessed the device performances of CIGS-based dual-junction tandem cells. The subcells of the tandem cells were assumed to exhibit state-of-the-art efficiencies in each bandgap. Additionally, we discussed how further improvements should be made to substantially overcome the efficiency of a single-junction CIGS solar cell. Highlights: Performances of CIGS-based tandem solar cells are simulated by the SCAPS-1D. Subcells are simulated to have state-of-the-art efficiencies up to date. Achievable efficiencies from the CIGS-based tandem cells are calculated. Relatively low efficiencies of the top subcells limit the tandem cells' efficiencies. It is also discussed that how further improvement from the top subcell is required. Abstract: In this work, we present SCAPS-1D simulations of Cu(In, Ga)Se2 -based dual-junction tandem cells. The purpose of this work is to assess the device performances of the Cu(In, Ga)Se2 -based tandem cells based on the fact that each subcell is simulated to yield a reported best efficiency at its bandgap. A method to build the J-V characteristics of tandem cells from individual J-V curves of subcells is also discussed. By thinning the absorber thickness of the top subcell, the current matching points among various bandgap combinations are examined. In spite of neither optical nor electrical loss between the top and bottom subcells, the device performances of the tandem devices do not substantially surpass the device performances of single-junction devices, which is ascribable to the relatively poor efficiencies of the wide-bandgap top subcells. We also discuss how further improvements in the wide-bandgap top subcells are needed to create a validity for making an effortful multi-junction device.